Exploring the landscape of adult autism research in psychology: a bibliometric and network analysis - Mota, Fabio Batista; Braga, Luiza Amara Maciel; Cabral, Bernardo Pereira (Frontiers in Psychology, 2024)
The global prevalence of autism spectrum disorder (ASD) is increasing. ASD manifests with persistent social communication and interaction challenges, limited interests, and repetitive behaviors. As the scientific literature on ASD in adults varies greatly, mapping the recent global research becomes valuable for enhancing comprehension of this subject. This study aims to map recent global scientific publications on ASD in adults. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, bibliometrics, and network analyses, we assessed 850 articles indexed in the Web of Science Core Collection between 2013 and 2022 assigned to the research area of psychology. Findings indicate an annual average growth of 11.69%. Key keywords include Emotion, Anxiety, and Depression, with Anxiety, Depression, and Mental Health as central nodes in the network. Rehabilitation, Behavioral Sciences, and Psychiatry frequently co-occur, and Psychology, Psychiatry, and ‘Neurosciences and Neurology’ are central nodes in the network of research areas. The United States of America and the United Kingdom lead in publications, with the United Kingdom being the most central country in the network. King’s College London and the University of California are the main research organizations, with King’s College London as the central node in the network. The American Psychiatric Association’s DSM-5-TR was the most cited reference in the period. This comprehensive analysis contributes to understanding the landscape of ASD research in adults, providing insights for future research and fostering collaborations.